Numerical modelling of low-temperature non-equilibrium plasma of pulsing corona and breakdown - Chyhin, V.I.; Karpyak, S.Y. (Condensed Matter Physics, 2007)
The method of determining an existence region of the non-equilibrium plasma of the pulsating negative corona
and breakdown is developed. The low-temperature non-equilibrium pulsing plasma of the point-to-plane negative
corona and a transition form to the breakdown in nitrogen-oxygen mixture are numerically simulated.
It is shown that plasma parameters are pulsing in time as well as in space. In the phase of corona pulse
peak, its position adjoins the cathode surface, no further than 0.01 cm. In the initial phase of breakdown, it
extends far beyond the surface, within the distance of 0.03 cm. At the same time, the electron temperature
changes in almost full anti-phase to the current: from 9100 K to 19000 K during the corona pulse peak and
from 6000 K to 20000 K in initial phases of the breakdown. The average plasma density changes in the range
7 × 10¹¹ − 8 × 10¹² cm⁻³ in the first case and 1 × 10¹³ − 5 × 10¹³ cm⁻³ in the case of breakdown. Запропоновано метод визначення областi iснування нерiвноважної плазми корони i газового пробиття. Низькотемпературна нерiвноважна пульсуюча плазма негативної корони мiж вiстрям i площиною та перехiдної форми до пробиття чисельно змодельована у сумiшi азоту i кисню. Показано, що параметри плазми пульсують, як у часi, так i в просторi розряду. Вона розмiщується безпосередньо бiля поверхнi катода, не далi, нiж 0.01 см у фазi пiку iмпульсу корони i високочастотного iмпульсу пробиття, i розширюється у межах 0.03 см вiд поверхнi до дрейфової областi у початковiй фазi пробиття. Температура електронiв змiнюється у майже повнiй антифазi до струму: вiд 9100 до 19000 К протягом пiку iмпульсу корони i вiд 6000 до 20000 К у початкових фазах пробиття. Усереднена густина плазми приймає значення 7 × 10¹¹ − 8 × 10¹² cm⁻³ у першому випадку i 1 × 10¹³ − 5 × 10¹³ cm⁻³ у випадку пробиття.